PENGARUH PENGGUNAAN BUKU AJAR BERMUATAN KECERDASAN KOMPREHENSIF DALAM MODEL PEMBELAJARAN PROBLEM SOLVING TERHADAP KOMPETENSI FISIKA PESERTA DIDIK KELAS X SMAN 1 PARIAMAN - Rif’il Husniyah; Hidayati Hidayati; Zulhendri Kamus (Universitas Negeri Padang, 2017)
Student competence on physics subject in the class X MIPA SMAN 1 Pariaman not as expected caused by several factors, teachers rarely use the varied learning model, and lack of students understanding on learning materials in solving problems. Lesson book contain comprehensif is one of the ways that is considered effective to improve the achievement of student physics competence. In the fact, lesson of the physics not be affective caused still use traditional models and dominan to result knowledge competence. Actually in the 2013 curriculum’s has several request for student : in the lesson physics student mus be active in observing, asking, trying, communicating and representation. The research type is quasi experiment research with non equivalent control group design. The study population is the students of class X MIPA SMAN 1 Pariaman registered in 2016/2017. Sampling is done by purposive sampling technique. The research instruments are final tests for knowledge competencies, observation sheets for attitude competencies, and scoring rubrics for skills competencies. The data obtained were analyzed using graphical analysis for attitude competence, two-averaging equality analysis and t correlation analysis for knowledge competence and two-averaging equality analysis for skill competence. Based on the data analysis could be presented the result of this research. using handout containing comprehensive intelligence has given significant effect toward Physics competency of students grade X SMAN 1 Pariaman with 0,05 signification level